2016
DOI: 10.1155/2016/4129864
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Photocatalytic Tests of N-Doped Zinc Oxide: A New Interesting Photocatalyst

Abstract: Fast and simple synthetic methods for the preparation of bare and N-doped zinc oxide, involving a stirring or microwave assisted process, are proposed. All samples were characterized by XRD analysis, BET, and DRS-UV-Vis spectroscopy. The photocatalytic activity of these nanostructured oxides was investigated using phenol and 2,4-dichlorophenol as model molecules under UV-A and visible light irradiation. N-doping in ZnO nanostructures provided a significant increase in phenol and 2,4-dichlorophenol degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Based on these results, the size of the crystallites is decreased in N-doped Cu2O/ZnO nanocomposite compared to the Cu2O and ZnO. The effect of decreasing the crystallite size may be ascribed to the insertion of nitrogen (incorporation of dopant) in Cu2O and ZnO lattices [32,33] and this was also confirmed in the photocatalytic degradation experiment. This insertion of nitrogen into the Cu2O and ZnO lattices can disturb the growth process of the particles, which might be the reason for the reduction of crystallite size in N-Cu2O/ZnO nanocomposite compared to Cu2O and ZnO nano-level particles.…”
Section: X-ray Diffraction (Xrd) Patterns Of the Nanomaterialssupporting
confidence: 54%
“…Based on these results, the size of the crystallites is decreased in N-doped Cu2O/ZnO nanocomposite compared to the Cu2O and ZnO. The effect of decreasing the crystallite size may be ascribed to the insertion of nitrogen (incorporation of dopant) in Cu2O and ZnO lattices [32,33] and this was also confirmed in the photocatalytic degradation experiment. This insertion of nitrogen into the Cu2O and ZnO lattices can disturb the growth process of the particles, which might be the reason for the reduction of crystallite size in N-Cu2O/ZnO nanocomposite compared to Cu2O and ZnO nano-level particles.…”
Section: X-ray Diffraction (Xrd) Patterns Of the Nanomaterialssupporting
confidence: 54%
“…Therefore, as a natural extension to the work of Liu et al and Sambrook et al, we have addressed ourselves to investigating the electronic band structure, density of states, electronic charge density distribution, photophysical and photocatalytic properties and thermoelectric properties of SrZnSO and CaZnSO using the first and second-principles methods. It has been reported that ZnS [7][8][9][10][11] and ZnO [12][13][14][15][16][17] are promising photocatalytic H2 production materials under visible light irradiation. Therefore, we have addressed ourselves to investigating the photocatalytic performance of SrZnSO and CaZnSO as ZnS and ZnO-containing materials.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The results showed that UV light does not discriminate bare and doped materials but the irradiation under vis light showed significant increase in phenol and 2,4-dichlorophenol degradation rate as well as release of chloride ions from 2,4-dichlorophenol in the presence of N-doped ZnO. 38 In the present work, the authors have investigated the influence of different halides on the properties of ZnO synthesized by polyol method using tetrabutylammonium halide (Cl, Br, and I) salts in comparison with pristine ZnO. The synthesized products were used as catalysts for photocatalytic decomposition of Rhodamine 6G (R6G) under UV light irradiation.…”
Section: Introductionmentioning
confidence: 94%